The Effect of Abdomınal Muscle Activity on Postural Control in Patients with Postmenopausal Osteoporosis - Musa Polat; Belgin Karoğlan (Galenos Yayinevi, 2022)
Objective:The trunk muscles are a component of the neuromuscular subsystem of postural control due to their location in the center of the kinetic chain. The aim of this study was to investigate the effect of abdominal muscle activity on postural control in patients with postmenopausal osteoporosis.Materials and Methods:Fifty-six postmenopausal osteoporosis patients with a fear of falling were included. Postural stability of the participants was evaluated with timed up and go test (TUG), Berg balance scale (BBS), and static balance index (SBI). Abdominal muscle activities were evaluated using a pressure biofeedback unit involving the performance of an abdominal drawing-in maneuver and posterior pelvic tilt movement. According to the postural stability test scores, the participants were divided into subgroups as high fall risk and low fall risk.Results:Twenty (35.7%) patients according to the TUG, 24 (42.8%) patients according to BBS, 18 (32.1%) patients according to SBI had a high risk of falling. In all subgroups analyzes, patients with a high risk of falling had more fall history (p=0.007, p<0.001, p<0.001, respectively), less pelvic tilt movement activity (p<0.001, both), and abdominal draw-in muscle activity (p<0.001, p=0.009, p<0.001, respectively).Conclusion:Patients with postmenopausal osteoporosis who have a high risk of falling have low abdominal muscle activities. While rehabilitating these patients might be performed core stabilization exercises that can increase the activation of the abdominal muscle activities.